Celebrate Thanksgiving Day - Kule, Elaine A. (Berkeley Heights, NJ : Enslow Publishers, 2006)
Describes the history behind Thanksgiving Day, explains the signs and symbols usually associated with the holiday, and tells about the thanksgiving festivals of other countries.
Happy Thanksgiving! -- Holiday history -- Cultural contributions -- Thanksgiving around the world -- Sights and symbols -- Thanksgiving today.
Includes bibliographical references (p. 110) and index.
Keywords: Thanksgiving Day